Penegakan Hukum Terhadap Kasus Pembunuhan Bayi Oleh Ibu Kandungnya (Studi Kasus di Polresta Surakarta dan Polres Wonogiri) - Wicaksana, Maharani Adhyaksantari, Muchammad Iksan, SH., MH (2017)
This research aims to know the profile of legal rule related to the criminal act of murdering a baby committed by its biological mother, to know the law enforcement of criminal act of murdering a baby in which the perpetrator is its biological mother in Polresta Surakarta and PolresWonogiri, as well as to know which factors cause the criminal act occurence of murdering a baby in which the perpetrator is its biological mother. The method of approach used by the writer is the juridical empirical approach. Kind of research used by the writer in this research is the descriptive research. The locations of the research are in Polresta Surakarta and Polres Wonogiri. This research used primary data source and secondary data source. The method of data collection in this research used the techniques of library study and field study through interview and observation with the sources who were considered as knowing the background of problem. Based on the results of the research and discussion, it can be concluded that the law enforcement by the police side in conducting the investigation process on the criminal act of murdering a baby committed by its biological mother covers: investigation, action, deep investigation, settlement, and case file delivery. The law enforcement in the implementation of article to suspect the suspect is the provision in Article 341 KUHP and Act Number 23 of 2002 regarding the Children Protection.